Identifikasi Bahaya Kontaminasi Staphylococcus aureus dan Titik Kendali Kritis Pada Pengolahan Produk Daging Ayam dalam Usaha Jasa Boga - Eni Harmayani; Eko Santoso; Tyas Utami; Sri Raharjo (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 1996)
The increasing demand of ready-to-eat food in big cities has led to the increasing number of food catering businesses. Ready to-eat foods prepared by food caterers have frequently been implicated as vehicles in outbreaks of foodborne diseases and their practices are potential vehicles of foodborne illness. Staphylococcus aureus is a foodborne pathogen which is of major concern for its ability to grow and produce heat resistance enterotoxin in variety of foods. Risks of eating ready-to-eat food, can be evaluated by the hazard analysis and critical control point (HACCP) approach. The objective of the study was to identify the hazard and critical control points relating to the production of several chicken meat products by food catering, especially from S. aureus contamination. Production of chicken satay, chicken meatball, and grilled chicken were evaluated in this study. The result indicated that raw chicken meats had total S. aureus of 10-106 CFUIg and total bacterial count of 107 CFUIg. During processing the number of S. aureus varied from 103 to 106 CFU/g according to the processing procedures. The number of total S. aureus of the finished products were < 102-103 CFU/g. During serving the products contained total bacterial count of 105 CFU/g and total S. aureus of 103-106 CFUIg. The D values of S. aureus at 45.60, and 65.5Â°C were 200,6.49, and 3.26 minutes, respectively. Evaluation on the processing procedures indicated that heating was the most important step in reducing bacterial population. The critical control points of these three products were refrigerating, cooking, distributing and serving.